La innovación productiva forestal y el desarrollo local a partir de la gobernanza de bienes comunes en la comunidad indígena de Nuevo San Juan Parangaricutiro, 1980-2008 - Castro Sánchez, Francisco Javier (Universidad Michoacana de San Nicolás de Hidalgo, 2012)
The socio-ecological systems are about to collapse. That is why, we ask ourselves these questions: which are the conditions that these maintainable systems have? How has the relationship process between the community inhabitants with common to explore the local inhabitants ? role in resilience to the common goods governance? This research analyses that the sustainability requires a close relationship between governance, innovation, common goods and development of the society, which have been the analysis axes that have a focal point in human resilience. For this research, we have focused our study in the indigenous community of Nuevo San Juan Parangaricutiro in the state of Michoacán. This place has driven a development model in order to support some social profits starting with the forest produce which has been in possession of local inhabitants since the 80 ?s in the 20 th century. The forward motion development pushed the institutions of this community to go ahead in a different way among the inhabitants which, in spite of having individual and communal benefits, it generated dilemmas that are still there and demand social interaction and benefits distribution of common goods. These dilemmas are in this perspective because of the decisions taken related to the use of common goods and above all, the forest produce which has some nuances, and is not always accepted in spite of the communal benefits. So, if resilience is an element which contributes to respond to time changes, how is it measured in front of a specific situation like the one of this community? Or, what is the human condition that contributes the most in resilience governance starting with the individual, familiar and social valuation? It was advisable to begin taking a sample of local inhabitants in order to realize the fortress and weakness in social interactions of life expectations.

Ante el entorno de riesgo en el deterioro o colapso en que se encuentran los sistemas socio-ecológicos, surgen reflexiones como las siguientes: ¿Cuáles son las condiciones que contribuyen a que estos sistemas sean sustentables?, ¿Cómo ha sido el proceso de relación entre los habitantes de comunidades con bienes comunes y su contexto de desarrollo? ¿Qué modelos de investigación pueden contribuir a explorar el papel que tienen los habitantes locales en la residencia de la gobernanza de los bienes comunes? En la presente investigación se plantea que para contribuir en la sustentabilidad debe existir una estrecha relación entre la gobernanza, la innovación, los bienes comunes y el desarrollo de una sociedad, los cuales han sido ejes de análisis que han tenido como punto focal la resilencia humana. Para esta investigación, el espacio de estudio ha sido la comunidad indígena de Nuevo San Juan Parangaricutiro, en el Estado de Michoacán, lugar en el que desde los años ochentas del siglo pasado, se impulsó un modelo de desarrollo que tuvo como sustento la generación de beneficios para el bienestar social a partir de la conservación y aprovechamiento de sus recursos forestales, los cuales son bienes comunes distribuidos en posesión de los habitantes locales. El impulso de un modelo de desarrollo orientó a ejercer de una forma diferente las instituciones en esta comunidad que, a pesar de generarse beneficios para los habitantes en lo general, propicio el establecimiento de dilemas entre lo individual y colectivo que prevalecen en la actualidad y mantienen escenarios que obligan a fortalecer las interacciones sociales, la distribución de los beneficios y el manejo de sus bienes comunes en equilibrio.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias del Desarrollo Regional
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/371; info:eu-repo/classification/cti/5; ININEE-D-2012-0007; Región Purépecha; Elementos sociales-ambientales; Manejo del territorio y de los recursos forestales; Perfil socio-económico; Innovación y desarrollo